2020
DOI: 10.1038/s41598-020-58106-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and potential mechanisms of highly antibiotic tolerant VBNC Escherichia coli induced by low level chlorination

Abstract: Escherichia coli is an important pathogenic indicator in drinking water. Viable but non-culturable (VBnc) E. coli induced by low level chlorination was found to have higher antibiotic tolerance. the emerging of VBnc bacteria in drinking water systems is posing challenges to the control of bio-safety. it is necessary to study the underlying mechanisms of VBnc state E. coli under actual residual chlorine condition of drinking water pipe network. In this study, we investigated the changes of morphology and gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…[31]. It is important to ensure effective disinfection to keep the water safe and to prevent re-contamination [32,33]. Often, for reasons of low cost, chlorination is carried out.…”
Section: Resultsmentioning
confidence: 99%
“…[31]. It is important to ensure effective disinfection to keep the water safe and to prevent re-contamination [32,33]. Often, for reasons of low cost, chlorination is carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many microorganisms, when subjected to stress may be present in drinking water in viable but noncultivable (VBNC) state (Ye et al 2020), where they cannot be grown on traditional culture media. Therefore, to evaluate the disinfection kinetics of novel compounds, alternative viability forms of waterborne microorganisms should be considered.…”
Section: Antimicrobial Properties Of Cnsmentioning
confidence: 99%
“…However, there remain disagreements about the effect of alternative sigma factors on the VBNC status. Lin, Ye, Chen, Zhang, and Yu (2017) reported that the -Escalona et al, 2006;Jameelah, Dewanti-Hariyadi, and Nurjanah, 2018;Munro et al, 1995;Up Boaretti et al, 2003Desnues et al, 2003;Lin et al, 2017 Catalase, kata [oxidative stress defense] Down Abe et al, 2006;Noor, Murata, and Yamada, 2009;Smith & Oliver, 2006Up Xu et al, 2018 Superoxide dismutase (sod) [oxidative stress defense] Down Noor et al, 2009;Zhao et al, 2016Up Meng et al, 2015 Electron transfer flavoprotein [energy metabolism] Down Lai, Chen, Lin, Chang, and Wong, 2009;Meng et al, 2015;Zhao et al, 2016 Up Postnikova, Shao, Mock, Baker, andNemchinov, 2015;Zhao et al, 2016 Transcriptional activator [transcription] Down Postnikova et al, 2015;Zhao et al, 2016Up Xu et al, 2018 Cytochrome b561 [energy metabolism] Up Lai et al, 2009;Zhao et al, 2016Down Postnikova et al, 2015 Type III secretion protein SpaO [secretion] Up Meng et al, 2015;Ye et al, 2020;Zhao et al, 2016Down Postnikova et al, 2015 Cell wall biosynthesis proteins (murA, dacB) [cell wall biosynthesis] Down Asakura, Ishiwa, et al, 2007 Up Hung, Jane, and Polyphosphate kinase, (ppk) [energy metabolism] Up Gangaiah, Kassem, Liu, & Rajashekara, 2009;Kassem, Chandrashekhar, and Rajashekara, 2013 Heat shock proteins Hsp [stress response] Up Capozzi et al, 2016; Heme export pr...…”
Section: Genes and Proteins Associated With The Vbnc Statusmentioning
confidence: 99%